PENGARUH PERUBAHAN ORGANISASI TERHADAP KINERJA PEGAWAI DI LINGKUNGAN KERJA UNIVERSITAS TEUKU UMAR - Fuadri, Fuadri (Universitas Teuku Umar, 2016)
Change the status of University College Teuku Umar became the government automatically has an influence on the changing demands of the organizational structure effectively and efficiently in accordance with service needs and organizational rules that apply. Organizational changes that occur in the work environment Teuku Umar University must also be accompanied by the provision of adequate human resources and competent, thus supporting the implementation of excellent service. No employee performance has not been able to run the organization function effectively and efficiently, thus greatly affecting service performance work environment Teuku Umar University. The results of the study in this paper shows that the factors that influence employee performance environment of the University of Teuku Umar include quality of work, attitude, initiative, responsibility, mastery of work, quantity of work and labor relations. The influence of the relationship of organizational change on employee performance seen in the regression coefficient obtained is Y = 0.771 + 0.778 X, where Y is the dependent variable in the form of employee performance and X is the independent variable or organizational change. This test also inform the level of closeness of their relationship by 67.20%.Keywords : Influence, organization, employee performance.